(1008) Economy of Education اقتصاد التعليم - Andrej Kamiac. (معهد التخطيط القومى, 2020)
So far, in the phases of development of human society, education has been playing mostly a human -cultural function and so it has for long been considered in the exclusive domain pedagogists. Apart from pedagogical science the other scientific disciplines rarely paid any attention to the development of learning and its methods.